Comparative Arterial Antithrombotic Activity of Clopidogrel and Acetyl Salicylic Acid in the Pig - Samama, Ch M; Bonnin, Ph; Bonneau, M; Pignaud, G; Mazoyer, E; Bailliart, O; Maffrand, J P; Viars, P; Caen, J P; Drouet, L O (Thrombosis and Haemostasis, 1992)
We investigated the comparative antithrombotic properties of clopidogrel, an analogue of ticlopidine, and aspirin, using the Folts' model on femoral arteries in 22 pigs. On each animal, clopidogrel or aspirin were used to treat the thrombotic process on the left femoral artery and to prevent this process on the right femoral artery. Sequentially: an injury and stenosis were carried out on the left femoral artery; the thrombotic process was monitored with a Doppler during a 30-min observation period for cyclic flow reductions or permanent cessation of flow; after the first cyclic flow reduction occurred, clopidogrel (5 mg kg-1) or aspirin (2.5, 5, 100 mg kg-1) were injected intravenously; if cyclic flow reductions were abolished, epinephrine (0.4 µg kg-1 min-1) was injected to try to restore cyclic flow reductions and/or permanent cessation of flow; then injury and stenosis were applied on the right femoral artery. Before and after injection of clopidogrel or aspirin, ear immersion bleeding times and ex-vivo platelet aggregation were performed. Clopidogrel (n = 7) abolished cyclic flow reductions in all animals and epinephrine did not restore any cyclic flow reduction. On the right femoral artery, cyclic flow reductions were efficiently prevented, even for two injuries. Basal bleeding time (5 min 28) was lengthened (>15 min, 30 min after clopidogrel and remained prolonged even after 24 h). ADP-induced platelet aggregation was inhibited (more than 78%). Comparatively, aspirin had a moderate and no dose-dependent effect. Aspirin 2.5 mg kg-1 (n = 6) abolished cyclic flow reductions in 2 animals, CFR reoccurred spontaneously in one animal and epinephrine restored it in a second animal. Aspirin 5 mg kg-1 (n = 6) abolished cyclic flow reductions in only 3 animals and epinephrine always restored it. Aspirin 100 mg kg-1 (n = 3) was unable to abolish cyclic flow reductions. On the right femoral artery, aspirin did not significantly prevent cyclic flow reductions which occurred in all animals after one (n = 14) or two injuries (n = 1), except for one animal. Basal bleeding time was lengthened but it shortened rapidly, reaching its basal value after 24 h. ADP-induced aggregation was not significantly inhibited, whereas arachidonic acid induced aggregation was always inhibited. Clopidogrel appears as a more potent antithrombotic drug than aspirin in this model, in treating and preventing spontaneous or epinephrine-induced cyclic flow reductions and lengthening bleeding time.